Constructional Impairments and Their Neural Correlates in Nondemented Adults With Cerebral Autosomal-dominant Arteriopathy With Subcortical Infarcts and Leukoencephalopathy. Issue 4 (26th December 2022) - De Lucia, Natascia; Ragno, Michele; Paci, Cristina; Cacchiò, Gabriella; Caiazzo, Anna Rita; Tiberi, Sara; De Rosa, Anna; Navarra, Riccardo; Caulo, Massimo; De Michele, Giuseppe; Trojano, Luigi
Abstract : Background: Cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a monogenic small-vessel disease that is characterized by a wide range of neurologic and neuropsychological impairments. Constructional impairments have been reported in some cases but have never been assessed systematically. Objective: To evaluate constructional abilities and their cognitive and neural correlates in nondemented individuals with CADASIL. Method: Thirty individuals with CADASIL who were not affected by clinically relevant cognitive deterioration and 30 healthy controls (HC) underwent an extensive cognitive assessment and paper-and-pencil visuoconstructional tasks in order to detect constructional impairments. Performance on the visuoconstructional tasks was correlated with the cognitive assessment scores and with quantitative indices of regional gray matter atrophy (obtained via FreeSurfer image analysis) and white matter involvement. Results: The individuals with CADASIL achieved significantly lower scores on the cognitive assessment compared with the HC. Poor visuoconstructional abilities were observed in seven (23.3%) of the individuals with CADASIL when performing the copy drawing task and in nine (30%) when performing the Rey Complex Figure Test. Logistic regression revealed that visuoconstructional impairments were significantly associated with scores on the Frontal Assessment Battery and the Attentional Matrices Test. Morphometric results revealed that scores on the visuoconstructional tasks were related to gray matter atrophy of the left frontal lobe and right parietal lobe. Conclusion: Impairments on visuoconstructional tasks are quite common in individuals with CADASIL, even in the lack of clinically relevant cognitive deterioration, and are critically related to frontal and parietal atrophy.